Rancang Bangun Aplikasi Pembelajaran Chord dan Melodi Gitar Berbasis Augmented Reality - Daniel Hero Fersil Punuindoong; Hira Meidia (Ultima Computing : Jurnal Sistem Komputer, 2017)
In this study, the application of the basic concepts of chord and melody guitar is made by using marker-based Augmented Reality method. Unity 3D is used to build the application and Vuforia is used as a library of Augmented Reality, where the application can recognize the marker as the basis of the virtual 3D objects rendering chord and melody guitar by using Android smartphone. There are several colours and numbers to make it easier to know the type and position of the fingers used in forming a chord or a melody. Index Terms- Augmented Reality, Guitar 3D Chord, Guitar 3D Melodi, Unity 3D, Vuforia, Android